Soybean Adaptation Mechanisms to Drought Through Stomatal Regulation, Carbon Assimilation, and Water Use Efficiency in Sustainable Farming Systems - Aminah, Aminah; Saida, Saida; Edy, Edy; Palad, Marliana S.; Nuraeni, Nuraeni; Haris, Abdul; Robbo, Anwar; Boceng, Annas; Fadel, Muh.; Akbar, Abd. (AGRIVITA Journal of Agricultural Science, 2026)
Unlike other crops, soybeans can be produced for both direct human consumption and industrial use. However, soybean production is highly sensitive to drought. This is because drought conditions can reduce photosynthesis and crop yield. This study aimed to investigate drought adaptations in soybean plants, including stomatal control, drought-induced carbon assimilation, and avoidance. The study was conducted in a greenhouse under controlled conditions using a split-plot design with 3 stress levels (100%, 50%, and 30% of field capacity), 4 varieties (Dering-1, Dering-2, Detap-1, and Argomulyo), and 2 stress periods (vegetative and generative). Strong variation in yield was observed across all drought-affected plant growth factors, including photosynthetic rate and grain yield. Under moderate stress conditions (achieving a 0.8 t/ha yield), the Detap-1 variety fully maintained photosynthetic capacity and appropriately modulated stomatal closure and stomatal regulation to achieve the most efficient water control. This leads to the conclusion that Detap-1 is best suited to the dryland conditions of the varieties studied due to its strong physiological adaptability.